El comte Arnau, la migració d'un mite. - DE LA PAU JANER MULET, MARIA (Scripta, 2016)
This article presents the study of the figure of Conde Arnau, the legendary hero from the Old Catalunya lands, whose history has passed through the centuries and has spreaded through a ballad and legendary spoken texts. The powerful and bad master, without scruples and friend of the devil, appears to his wife after death. He comes out of hell, like a spirit in pain, wandering the land on a horse of flames. The ballad was composed in form of a dialogue between the lady and the spirit of the Conde. Through the legendary history of the Conde Arnau, the villagers questioned the legitimity of the Master, who was unable tu fulfelt his promises. In inmigrated to the island of Mallorca, the legend is consolidated in one identified historical character, which was concentrated in this legendary conde badness.